Symbols and logos used by electoral lists participating in the 2009 provincial council elections in Baghdad Governorate (Journal of the College of Basic Education, 2024)
The research dealt with identifying the types of symbols and the contents of the slogans used by the electoral lists that participated in the 2009 provincial council elections in Baghdad Governorate. The research raised a main question: What symbols and slogans were used by the electoral lists participating in the 2009 provincial council elections in Baghdad Governorate? The survey method was used, as all electoral lists that participated in the Baghdad Provincial Council elections were studied. And using the content analysis method to classify symbols, slogans, and names of electoral lists to answer the research questions. One of the most important results was that 85.71% of electoral lists used symbols and slogans, compared to 14.28% that did not use them. It also turned out that the symbols and slogans were close and similar. This similarity in symbols, slogans and names did not give a clear image of the electoral lists to the Iraqi voter, but rather gave a blurry and unclear image, and the voter was confused about the electoral lists with their similar names, symbols and slogans, in addition to the large number of candidates and lists, which further confuses the mind of the voter Iraqi.